3D cadastres: legal approaches and necessary reforms. Issue 338 (September 2014) - Kitsakis, D.; Dimopoulou, E.
<x content-type="archive" xml:space="preserve">Abstract</x> The increased number of amenities in modern societies involves the intense exploitation of land above and below the earth's surface, resulting in complex constructions and proprietary status. Therefore, each country's legal and cadastral framework needs to be amended in order to cope with the emerging conditions. This paper aims to summarise the regulations that define the creation of multi-surface property units in Common and Civil Law jurisdictions, in order to aggregate the legal instruments used in each one. Civil Law jurisdictions are influenced by the Roman principles which impose the right of accession and allow vertical ownership for the owner of the surface parcel. Common Law jurisdictions do not strictly relate ownership of immovable property to the ownership of the surface parcel. Significant research has been conducted in many countries which ended up either in specialised legal and cadastral reforms introducing property forms, such as condominium schemes, housing companies and limited rights in rem, or through the introduction of 3D property units. The latter approach which was firstly introduced in Common Law jurisdictions is gradually adopted by Civil Law jurisdictions. Both jurisdictions share similar concepts although they are differentiated in structural, terminological, cadastral infrastructure and implementation aspects.